A review of the pesticide MCPA in the land‐water environment and emerging research needs. (3rd December 2019) - Morton, Phoebe A.; Fennell, Chris; Cassidy, Rachel; Doody, Donnacha; Fenton, Owen; Mellander, Per‐Erik; Jordan, Phil
Abstract: Due to its high solubility and poor adsorption to the soil matrix, the post‐emergence herbicide 2‐methyl‐4‐chlorophenoxyacetic acid (MCPA) is susceptible to transport into surface and groundwater bodies, where it can result in compromised water quality and breaches of legislative standards. However, there is still poor understanding of catchment scale dynamics and transport, particularly across heterogeneous hydrogeological settings. While it is known that MCPA degrades under aerobic conditions, negligible breakdown can occur in anaerobic environments, potentially creating a legacy in saturated soils. Fast runoff pathways post application are likely transport routes, but the relative contribution from the mobilization of legacy MCPA from anaerobic zones has yet to be quantified, making the delineation of MCPA sources encountered during monitoring programs challenging. While ecotoxicological effects have been examined, little is known about the interaction of MCPA (and its degradation products) with other pesticides, with nutrients or with colloids, and how this combines with environmental conditions to contribute to multiple stressor effects. We examine the state of MCPA knowledge, using case study examples from Ireland, and consider the implications of its widespread detection in waterbodies and drinking water supplies. Research themes required to ensure the sustainable and safe use of MCPA in an evolving agricultural, social and political landscape are identified here. These include the need to identify mitigation measures and/or alternative treatments, to gain insights into the conditions governing mobilization and attenuation, to map pathways of migration and to identify direct, synergistic and antagonistic ecotoxicological effects. This article is categorized under: Water and Life > Stresses and Pressures on Ecosystems Science of Water > Water Quality Abstract : The soluble herbicide 2‐methyl‐4‐chlorophenoxyacetic acid (MCPA) is poorly understood, yet frequently used in agriculture and causes breaches in legislative water quality standards. Identification of mitigation measures requires further insights into MCPA's degradation and transportation pathways and ecotoxicological effects.